2018
DOI: 10.1101/380410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drosophila insulin-like peptide dilp1 increases lifespan and glucagon-like Akh expression epistatic to dilp2

Abstract: Insulin/IGF signaling (IIS) regulates essential processes including development, metabolism, and aging. The Drosophila genome encodes eight insulin/IGF-like peptide (dilp) paralogs, including tandem-encoded dilp1 and dilp2. Many reports show that longevity is increased by manipulations that decrease DILP2 in adults. In contrast, dilp1 is expressed primarily in pupal stages, but also during adult reproductive diapause, although we find that dilp1 is also highly expressed in adult dilp2 mutants under non-diapaus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…Several secreted proteins also have been reported to regulate AKH secretion. dILP2 induces AKH expression in CC in a dILP1-dependent fashion in adult Drosophila (102). Similarly, Upd2 secreted from skeletal muscle promotes AKH secretion from CC in adults (20).…”
Section: Regulation Of Akh Signalingmentioning
confidence: 95%
“…Several secreted proteins also have been reported to regulate AKH secretion. dILP2 induces AKH expression in CC in a dILP1-dependent fashion in adult Drosophila (102). Similarly, Upd2 secreted from skeletal muscle promotes AKH secretion from CC in adults (20).…”
Section: Regulation Of Akh Signalingmentioning
confidence: 95%
“…Crz is released during stress to mobilize energy stores and fuel locomotion, it could also act on Va neurons to stimulate CAPA release, which would aid in expulsion of metabolic waste 18 products via the Malpighian tubules. Moreover, Crz could also independently modulate CAPA release during desiccation and cold stress.…”
Section: How Does Systemic Crz Signaling To the Capa-expressing Va Nementioning
confidence: 99%
“…Although the insect pars intercerebralis-pars lateralis and corpora cardiaca are considered the functional equivalents of mammalian hypothalamus and pituitary gland, respectively [16], no explicit stress axis or stress hormones have yet been identified in insects. Much progress has been made on the roles of DILPs and AKH (insect ortholog of mammalian gonadotropin-releasing hormone; GnRH) in metabolism, nutritional stress and longevity [5,10,[17][18][19]. For instance, both these signaling systems regulate starvation-induced hyperactivity/food search in Drosophila [20].…”
Section: Introductionmentioning
confidence: 99%
“…The dilp1 mutant flies have normal lifespan, and so do dilp1-dilp2 double mutants, suggesting that loss of dilp1 rescues the lifespan extension of dilp2 mutants. This study also found that dilp1 is downstream of dilp2 in regulation of AKH [535], another known positive regulator of longevity [533]. It was suggested that DILP2 indirectly regulates AKH by repressing expression of DILP1 (that normally upregulates AKH) and also that DILP1 normally represses JH, which results in prolongevity effects [535].…”
Section: 1 4 Insulin Signaling In Lifespan and Diapausesupporting
confidence: 55%
“…Also some other gene manipulations that decrease dilp2 expression increase lifespan: overexpression of FOXO in the fat body and JNK in the IPCs [634][635][636]. In contrast, it was recently shown that dilp1 promotes longevity [535]. The dilp1 mutant flies have normal lifespan, and so do dilp1-dilp2 double mutants, suggesting that loss of dilp1 rescues the lifespan extension of dilp2 mutants.…”
Section: 1 4 Insulin Signaling In Lifespan and Diapausementioning
confidence: 99%